Exhaust Gas Analysis of Firewood Combustion Processes: Application of a Robust Thermoelectric Gas Sensor - Binayak Ojha (Proceedings, 2017)
The quality of firewood combustion processes can be considerably improved by automated control of the combustion air streams. For this purpose, continuous flue gas analysis using in-situ sensors is essential. In order to monitor the unburned exhaust gas components like carbon monoxide (CO) and hydrocarbons (CxHy), for the first time a novel thermoelectric gas sensor was applied directly in the exhaust gas. The sensor is made of high temperature stable materials and promises the needed robustness. Here, the sensor signal is compared to flue gas analysis data from FTIR measurements during a wood-log batch firing experiment. An impressive correlation between both data was found.